2018
DOI: 10.4049/jimmunol.1701216
|View full text |Cite
|
Sign up to set email alerts
|

Innate Recognition of the Microbiota by TLR1 Promotes Epithelial Homeostasis and Prevents Chronic Inflammation

Abstract: There is cross-talk between the intestinal epithelium and the microbiota that functions to maintain a tightly regulated microenvironment and prevent chronic inflammation. This communication is partly mediated through the recognition of bacterial proteins by host-encoded innate receptors, such as TLRs. However, studies examining the role of TLR signaling on colonic homeostasis have given variable and conflicting results. Despite its critical role in mediating immunity during enteric infection of the small intes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 61 publications
1
22
0
2
Order By: Relevance
“…TLR1 recognizes bacterial lipoproteins and peptidoglycans and is known to mediate cytokine production along with TLR2. Recently, TLR1 has been reported to play an important role in the regulation of chronic inflammation by sensing the gut microbiota (26). In another study, TLR1 signaling was shown to regulate inflammation during intestinal infection, and TLR1 deficiency led to vulnerability to intestinal inflammation and tissue injury by dysbiosis (27).…”
Section: Discussionmentioning
confidence: 99%
“…TLR1 recognizes bacterial lipoproteins and peptidoglycans and is known to mediate cytokine production along with TLR2. Recently, TLR1 has been reported to play an important role in the regulation of chronic inflammation by sensing the gut microbiota (26). In another study, TLR1 signaling was shown to regulate inflammation during intestinal infection, and TLR1 deficiency led to vulnerability to intestinal inflammation and tissue injury by dysbiosis (27).…”
Section: Discussionmentioning
confidence: 99%
“…Further evidence gleaned from genetic knockout models have helped highlight the differential effects of TLRs on mucin regulation. For instance, naïve Tlr1 −/− mice have defective production and/or secretion of MUC2 in the colon leading to a patchy and significantly depleted mucus layer ( 67 ). Tlr5 −/ − mice display a mosaic phenotype; a subset of these mice develop spontaneous colitis while the majority do not.…”
Section: Immunological Regulation Of Mucin Productionmentioning
confidence: 99%
“…IBD patients have increased levels of TLR4 expression, and lower level of TLR2 and TLR5 in epithelial cells, while TLR4 was shown to be expressed in the apical surface of epithelial cells (28). Current studies have demonstrated the importance of TLR1 in the prevention of gut inflammation (29). In addition to NOD-2 mutations, abnormal mucosal NLRP3 activity has been reported in IBD and in experimental colitis; GWAS studies revealed polymorphisms in these receptors (3033).…”
Section: Non-immune Cells Involved In Gut Inflammationmentioning
confidence: 99%